Beginning PHP and PostgreSQL E-Commerce - Darie, Cristian (Apress, 2012)
Welcome to Beginning PHP and PostgreSQL E-Commerce: From Novice to Professional! The explosive growth of retail over the Internet is encouraging more small- to medium-sized businesses to consider the benefits of setting up e-commerce web sites. Although there are great and obvious advantages to online retail, there are also many hidden pitfalls that you might encounter when developing a retail web site. This book provides you with a practical, step-by-step guide to setting up an e-commerce web site. Guiding you through every step of the design and build process, this book will have you building high quality, extendable e-commerce web sites quickly and easily. Over the course of the book, you will develop all the skills necessary to get your business up on the web and available to a worldwide audience. We present this information in a booklong case study, the complexity of which develops as your knowledge increases through the book. The case study is presented in three phases. The first phase focuses on getting the site up and running as quickly as possible and at a low cost. Although not yet full-featured, at the conclusion of this phase, your site will be capable of accepting PayPal payments, enabling you to begin generating revenue immediately.